Physical activity and sleep during the first week of anorexia nervosa inpatient care - Billy Langlet (Public Library of Science (PLoS), 2021)
Background Individuals with Anorexia Nervosa are often described as restless, hyperactive and having disturbed sleep. The result reproducibility and generalisability of these results are low due to the use of unreliable methods, different measurement methods and outcome measures. A reliable method to measure both physical activity and sleep is through accelerometry. The main purpose of the study was to quantify the physical activity and sleeping behaviour of anorexia nervosa patients. Another purpose was to increase result reproducibility and generalisability of the study. Material and methods Accelerometer data were collected from the first week of treatment of anorexia nervosa at an inpatient ward. Raw data from the Axivity AX3© accelerometer was used with the open-source package GGIR for analysis, in the free statistical software R. Accelerometer measurements were transformed into euclidean norm minus one with negative values rounded to zero (ENMO). Physical activity measurements of interest were 24h average ENMO, daytime average ENMO, inactivity, light activity, moderate activity, and vigorous activity. Sleep parameters of interest were sleep duration, sleep efficiency, awakenings, and wake after sleep onset. The sleep duration of different age groups was compared to recommendations by the National Sleep Foundation using a Fisher’s exact test. Results Of 67 patients, due to data quality 58 (93% female) were included in the analysis. Average age of participants was 17.8 (±6.9) years and body mass index was 15.5 (±1.9) kg/m2. Daytime average ENMO was 17.4 (±5.1) mg. Participants spent 862.6 (±66.2) min per day inactive, 88.4 (±22.6) min with light activities, 25.8 (±16.7) min with moderate activities and 0.5 (±1.8) min with vigorous activities. Participants slept for 461.0 (±68.4) min, waking up 1.45 (±1.25) times per night for 54.6 (±35.8) min, having an average sleep quality of 0.88 (±0.10). 31% of participants met sleep recommendations, with a significantly higher number of 6–13 year old patients failing to reach recommendations compared to 14–25 year old patients. Conclusion The patient group spent most of their time inactive at the beginning of treatment. Most patients failed to reach sleep recommendations. The use of raw data and opensource software should ensure result reproducibility, enable comparison across points in treatment and comparison with healthy individuals.